Every living thing - Herriot, James (New York : St. Martin's Press, 1992)
Veterinarian Herriot continues his delightful recollections of his work among the animals & people of the Yorkshire Dales in the 1950s.
Keywords: Herriot, James; Veterinary medicine -- England -- Yorkshire -- Anecdotes; Veterinarians -- England -- Yorkshire -- Biography